The Effectiveness of using Android Based Chemical Ludo Game Media Reduction and Oxidation Reaction Material on Students Learning Outcomes - Sari, Indah Fedya; Iswendi, Iswendi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This research follow up research development of Educational Design Research with Plomp model that has been done the validity and practicality test but hasn’t been tested effectiveness using the android based chemical ludo game media for reduction and oxidation reactions material on student learning outcomes for class X SMA/MA. This aims for reveal the level effectiveness using the android based chemical ludo game media on reduction and oxidation reaction material to learning outcomes of class X SMA/MA.The design used was pretest-posttest control group design with random sample group. The sample of research were class X MIPA 4 with 34 students and X MIPA 3 with 34 students at SMAN Binaan Khusus. The research instrument is instrument test and questionnaires. The data using analyzed with N-Gain test and hypothesis test (t-test). N-Gain the experimental class was 0.79 with high category and the control class was 0.47 with medium category. The hypothesis testing which was carried out with the t-test with tcount (7.84527) > ttable (1.668) at the real level α = 0.05. So the android based chemical ludo game media material for reduction and oxidation reactions effective in increasing learning outcomes for students significantly in the cognitive domain class X SMA/MA.